(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The article provides a scientific analysis of folklore motives of proverbs in "Kutadgu bilig". At the same time, the problems of translating articles into foreign languages were discussed. Recommendations for future translations are given.